2021
DOI: 10.1063/5.0029486
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials-based formulations and surfaces to combat viral infectious diseases

Abstract: Rapidly growing viral infections are potent risks to public health worldwide. Accessible virus-specific antiviral vaccines and drugs are therapeutically inert to emerging viruses, such as Zika, Ebola, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Therefore, discovering ways to prevent and control viral infections is among the foremost medical challenge of our time. Recently, innovative technologies are emerging that involve the development of new biomaterial-based formulations and surfaces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 133 publications
0
17
0
Order By: Relevance
“…Several inorganic nanoparticles, including gold, silver, silica and iron have been formulated as vaccine delivery systems [ 79 ]. Influenza virus M2 membrane protein immobilized on gold-nanoparticles induced protective immunity against influenza A subtypes [ 80 ].…”
Section: Nanotechnology-based Vaccine Delivery Platforms and The Development Of An Nkt Cell-based Nanovaccinementioning
confidence: 99%
“…Several inorganic nanoparticles, including gold, silver, silica and iron have been formulated as vaccine delivery systems [ 79 ]. Influenza virus M2 membrane protein immobilized on gold-nanoparticles induced protective immunity against influenza A subtypes [ 80 ].…”
Section: Nanotechnology-based Vaccine Delivery Platforms and The Development Of An Nkt Cell-based Nanovaccinementioning
confidence: 99%
“…The observed effects were attributed to the electrostatic and hydrophobic interaction between the glycosaminoglycan coated nanoparticles and the virus (HSV-1 and 2) [ 58 ]. However, such coating technologies suffer from lack of durability and have limited mechanical stability, and thereby, design and fabrication of more robust antiviral surfaces are required [ 52 , 53 , 59 ].
Figure 6 SEM images of nanostructured aluminum surfaces after wet-etching.
…”
Section: Survival Of Coronavirus On Engineered Surfaces: Towards Designing Antiviral Surfacesmentioning
confidence: 99%
“…This fact marks the importance of fabricating antiviral surfaces. Such surfaces are said to exhibit virucidal properties, i.e., surface properties due to which they become less conducive to the survival of virus and the viral load deposited on such surfaces diminishes rapidly [52,53]. For example, polymer surfaces rich with polycations were found to cause rapid viral disintegration [54,55].…”
Section: Survival Of Coronavirus On Engineered Surfaces: Towards Designing Antiviral Surfacesmentioning
confidence: 99%
“…Furthermore, a recent study proposed that the use of a variety of physical techniques such as photolithography and laser surface modification, in conjunction with ion beam–assisted deposition, can be used to evolve biomaterial surfaces or self-cleaning surfaces with suitable topographical features and controlled cell adhesion (Kumari and Chatterjee 2021 ). In this sense, the antiviral behavior of aluminum surfaces with appropriately aligned ridges has been studied against SARS-CoV-2, and it was found that the self-disinfecting surfaces with coated nanoparticles are substantially effective against SARS-CoV-2 (Hasan et al 2020a ; Hasan et al 2020b ).…”
Section: Mitigation Strategies To Reduce the Deleterious Consequences Of Disinfectants In Humans And The Environmentmentioning
confidence: 99%